DETERMINANTS OF ENERGY-SAVING BEHAVIOR AMONG LECTURERS: THE ROLES OF SOCIAL NORMS, HABITS, AND ENVIRONMENTAL AWARENESS IN STMIK CAMPUSES - Feriani Astuti Tarigan; Hendri; Deva Djohan; Nasib; Kabiru Sa'ad Sa'id (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study examines the influence of social norms, habit, and environmental awareness on energy saving behavior among lecturers in three accredited Informatics and Computer Management Colleges in Medan, with a total population of 83 lecturers. Using a census technique, the entire population was sampled. Data were collected through a standardized questionnaire and analyzed using multiple linear regression. The results reveal that social norms have a significant positive effect on energy-saving behavior, indicating that the energy-saving behavior of lecturers is influenced by social norms and pressures within the academic environment. Habit has the most dominant positive influence, suggesting that everyday habits play a crucial role in forming energy-saving behavior. Environmental awareness also has a substantial positive effect, confirming that the higher the environmental awareness, the greater the tendency of lecturers to save energy. Simultaneously, these three variables explain a considerable proportion of the variance in energy saving behavior, demonstrating that energy conservation is driven by the integration of social influence, behavior automatization, and environmental cognition. This study contributes theoretically to the development of environmental behavior literature in higher education and practically to the reinforcement of green campus policies. The findings suggest that institutional leaders should establish pro-environmental social norms, create energy-efficient standard operating procedures, implement real-time feedback systems, and organize regular environmental awareness programs to enhance lecturers' motivation toward sustainable behavior. The study highlights that higher education sustainability is driven not only by institutional rules but also by the active behavioral participation of academic staff in the workplace.